Differential effect on myelination through abolition of activity‐dependent synaptic vesicle release or reduction of overall electrical activity of selected cortical projections in the mouse. Issue 3 (22nd March 2019) - Korrell, Kim V.; Disser, Jolande; Parley, Kristina; Vadisiute, Auguste; Requena‐Komuro, Maï‐Carmen; Fodder, Harriet; Pollart, Charlotte; Knott, Graham; Molnár, Zoltán; Hoerder‐Suabedissen, Anna
Abstract: Myelination of axons by oligodendrocytes in the central nervous system is crucial for fast, saltatory conduction of action potentials. As myelination is central for brain development and plasticity, and deficits are implicated in several neural disorders such as multiple sclerosis, major depressive disorder, bipolar disorder and schizophrenia, it is important to elucidate the underlying mechanisms regulating myelination. Numerous mechanisms have been proposed by which the communication between oligodendrocytes and active axons may regulate the onset and maintenance of activity‐dependent myelination. We compared two models of 'silencing' layer V and/or VI cortical projection neurons from early stages by either decreasing their excitability through Kir2.1 expression, an inward rectifying potassium channel, introduced through in utero electroporation at embryonic day (E)13.5, or inhibiting regulated vesicular release through Cre‐dependent knock‐out of synaptosomal associated protein 25 kDA (SNAP25). SNAP25 is a component of the soluble N‐ethylmaleimide fusion protein attachment protein receptor (SNARE) complex, which, among others, is needed for calcium‐dependent regulated vesicle release from synapses. In layer VI cortical projection neurons in the Ntsr1‐Cre;Ai14;Snap25 fl/fl mouse, we found that inhibiting regulated vesicular release significantly decreased the amount of myelin basic protein (MBP, used as marker for myelination) and the amount of myelinated projections at postnatal day (P)14 without affecting the initial timing of onset of myelination in the brain (at P7/P8). Additionally, overall oligodendrocyte maturation appears to be affected. A strong trend towards reduced node of Ranvier (NoR) length was also observed in Ntsr1‐Cre;Ai14;Snap25 fl/fl corpus callosum. An equally strong trend towards reduced NoR length was observed in Rbp4‐Cre;Ai14;Snap25 fl/fl corpus callosum at P14, and the g‐ratio in the spinal cord dorsal column was reduced at P18. However, no measurable differences in levels of MBP were detected in the striatum when comparing Rbp4‐Cre;Ai14;Snap25 fl/fl and control brains. Conversely, Kir2.1 in utero electroporation at E13.5 did not significantly affect the amount of MBP or number of myelinated callosal axons at P14 but did significantly decrease the NoR length measured in the corpus callosum. It therefore seems likely that the excitability of the neuron can potentially perform a modulating function of myelin characteristics, whereas regulated vesicular release has the potential to have a more pronounced effect on overall myelination, but in a cell‐type specific manner. Abstract : Node of Ranvier length on myelinated axons in the corpus callosum of mice is decreased after reduction in axonal excitability via Kir2.1 electroporation, or after abrogation of regulated synaptic vesicle release via SNAP25 conditional knock‐out in selected cortical neuronal populations.